(3GdfhQ GdLdj aj GdfSH GdTQja GdfHhjs - (3MSf Hf YHO Gddg Hf eMeO GdHNTj, CHh GdNdGU,J (B1190 (3g` s ((3bQjI QGe MeOGf s)
(3ChdgG (B:s
(3GdMeO ddg CeG HYO , ajbhd CHh GdENdGU Efi deG hbaJ Ydi CbGhjd GdYdeGA GdeUWai heG Jcde Hg HYV GdedMOjf CMHHJ JfRjg SGMJgG hCPcQ edNU eG EYJeOg GdSjhWi ai QSGdJg GdeSeGg H(B" (3eSGdc GdMfaG (B" s
(3BNQgG (B:s
(3hGdYLH ef Ydi GdbGQi heG UfY ai QSGdJg GdeNGdaI ddCUhd hdYd GdHQhOI CKQJ ai QCSI aGNJd Ybdg JeJ s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ HYV cdeGJgG HGdMeQI HBNQgG aUd ai jhe GdLeYI heG jJYdb Hg hjbY ai (B11 (3hQKbIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs